Composition of docosahexaenoic acid, eicosapentaenoic acid and palmitoleic acid in Eucheuma denticulatum, Sargassum polycystum and Caulerpa lentillifera ethanolic extracts by LC-ESI-MS/MS - Balasubramaniam, Vimala; Lee, June Chelyn; Brownlee, Iain A.; Mohd Noh, Mohd Fairunizal; Ahmad, Syahida; Ismail, Amin (SciTechnol, 2018)
Omega-3 and omega-7 fatty acids have been linked to health benefit in humans. Seaweeds are potential source of fatty acids. Thus, in the current study, a rapid and highly selective method with minimal sample preparation based on liquid chromatographic electrospray ionization tandem mass spectrometry (LC/MS/MS) has been developed and validated for the quantitative determination of docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and palmitoleic acid (PA) in Eucheuma denticulatum, Caulerpa lentillifera and Sargassum polycystum ethanolic extracts. The levels of DHA, EPA and PA were in ranges of 6.0-7.0 μg/100 g DW, 51.0- 122.0 μg/100 g DW and 5.0-690.0 μg/100 g DW respectively in the three species of seaweed tested. The standard calibration curves for PA, DHA and EPA were linear (R2 > 0.99) over the concentration ranged between 0-3.00 ng μL-1, respectively, satisfactory recoveries (> 77%), low detection (0.0047- 0.0175 ng μL-1) and quantification limits (0.0156-0.0580 ng μL-1) (LOD and LOQ, respectively). These results indicated that LC-ESI-MS/MS was successfully applied to the analysis of the selected fatty acids in the three groups of seaweeds.